2012
DOI: 10.1371/journal.pone.0051283
|View full text |Cite
|
Sign up to set email alerts
|

Atbf1 Regulates Pubertal Mammary Gland Development Likely by Inhibiting the Pro-Proliferative Function of Estrogen-ER Signaling

Abstract: ATBF1 is a candidate tumor suppressor that interacts with estrogen receptor (ER) to inhibit the function of estrogen-ER signaling in gene regulation and cell proliferation control in human breast cancer cells. We therefore tested whether Atbf1 and its interaction with ER modulate the development of pubertal mammary gland, where estrogen is the predominant steroid hormone. In an in vitro model of cell differentiation, i.e., MCF10A cells cultured in Matrigel, ATBF1 expression was significantly increased, and kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 71 publications
(106 reference statements)
3
29
0
5
Order By: Relevance
“…Development-We previously measured Zfhx3 mRNA expression at different stages of mammary gland development and found that the Zfhx3 mRNA level varies at different stages, being the highest in late pregnancy and lactation (20). Here we determined Zfhx3 protein expression.…”
Section: Expression Of Zfhx3 Protein During Mammary Glandmentioning
confidence: 95%
See 4 more Smart Citations
“…Development-We previously measured Zfhx3 mRNA expression at different stages of mammary gland development and found that the Zfhx3 mRNA level varies at different stages, being the highest in late pregnancy and lactation (20). Here we determined Zfhx3 protein expression.…”
Section: Expression Of Zfhx3 Protein During Mammary Glandmentioning
confidence: 95%
“…Breeding, genotyping, and preparation of mice with MMTV-Cre-mediated mammary-specific knock-out of Zfhx3 were previously described (20). All mice were fed with pathogen-free food and water and were closely monitored and humanely euthanized.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations